Invitin Project: Scrum Framework Implementation in a Software Development Project Management - Hidayah, Nadila Wirdatul; Sasmita, Rizka Rahayu; Mayangsari, Mustika Kurnia; Kusuma, Oskar Galih Wira; Rante, Hestiasari; Fariza, Arna (Politeknik Negeri Ujung Pandang, 2022)
The printed invitation is commonly used in our community to invite others to special events. In Indonesian society, this has happened inviting someone from door-to-door by sending printed invitations. Due to rapid information technology development, we proposed a website-based online invitation platform, Invitin. In general, the Invitin project has three main actors, which are customer, customer service, and admin. The methodology that we used was based on the SDLC (Software Development Life Cycle) and applied Scrum framework. Implementing the Invitin project using Scrum helps to organize development tasks easier and provides other benefits in some cases. Thus, Scrum increases our team productivity to develop a high-quality dynamic website application.